2015
DOI: 10.1002/eji.201445243
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome immunosubunits, PA28 and ER‐aminopeptidase 1 protect melanoma cells from efficient MART‐126‐35‐specific T‐cell recognition

Abstract: Eur. J. Immunol. 2015. 45: 3257-3268 IntroductionThe differentiation antigen melanoma antigen recognized by T cells/melanoma antigen A (thereafter named MART-1) has been a major target in antigen-specific immunotherapy of malignant melanoma and in particular its immunodominant HLA-A*0201-restricted CD8 + T-cell epitope MART-1 26(27)-35 [1,2]. But clinical efficacy of different MART-1-specific therapies has only been limited. In vitro studies employing high-affinity MART-1-specific CD8 + T-cell clones demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 48 publications
3
51
0
4
Order By: Relevance
“…Upon exposure to IFN‐γ, ERAP1 expression was enhanced in both Ma‐Mel‐86a cells and Ma‐Mel‐63a cells (Fig. D) and also in UKRV‐Mel‐15a cells as shown before . Since ERAP activity could be influenced by the various polymorphisms that these enzymes have, we analyzed the ERAP1 alleles present in the investigated cell lines.…”
Section: Resultsmentioning
confidence: 56%
“…Upon exposure to IFN‐γ, ERAP1 expression was enhanced in both Ma‐Mel‐86a cells and Ma‐Mel‐63a cells (Fig. D) and also in UKRV‐Mel‐15a cells as shown before . Since ERAP activity could be influenced by the various polymorphisms that these enzymes have, we analyzed the ERAP1 alleles present in the investigated cell lines.…”
Section: Resultsmentioning
confidence: 56%
“…Taken together, the report by Keller et al. indicates that a combination of proteolytic activities induced by IFN‐γ can result in immunoediting of tumors and promote immune evasion. This form of immunoediting might explain the curious case of a patient, identified as VMM5, who had a melanoma recur twice over a 12‐year period .…”
mentioning
confidence: 81%
“…In additional experiments, Keller et al. found that β1i‐ and/or β2i‐containing HeLa cells poorly activated MART‐1 26—35 ‐specific CD8 + T cells. Accordingly, 20S proteasomes isolated from these cells yielded low‐to‐no MART‐1 26—35 epitope, owing to poor liberation of the carboxyl‐terminus by β2i, as well as the amino‐terminus by both β1i and β2i (Fig.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…24 h post seeding cells were transfected with (i) PA28α and PA28β siRNA (each 30nM, ON-TARGET plus—SMART pool, Dharmacon) or with (ii) control siRNA (60 nM, ON-TARGET plus—SMART pool, Dharmacon) using X-tremeGENE siRNA transfection reagent (Roche) and cultured for 72 hours. For overexpression studies, HeLa cells were seeded into 12-well plates at a density of 1.5 x 10 5 cells per well and transfected the following day with (i) hPA28α-pcDNA3.1 and hPA28β-pcDNA3.1 (0.25 μg each/well) [35] or (ii) mPA28α-pSG5 and mPA28β-pSG5 (0.25 μg each/well) for 24 hours using polyethylenimine (Polysciences). Empty pcDNA3.1 and pSG5 served as a control, respectively.…”
Section: Methodsmentioning
confidence: 99%